Development of Tests Based on Proprofs Digital Media to Measure Higher Order Thinking Skills (HOTS) of Students in Science Learning - Donna Boedi Maritasari; Aswasulasikin; Alfiatun Lailani (Postgraduate, University of Mataram, 2025)
The development of digital technology in the world of education has been very rapid. Teachers must be able to adapt to the use of innovative and creative learning technology. In addition to the learning process that requires technology integration, learning evaluation also needs to be integrated with technology so that students are accustomed to working on questions through technology integration. One of the learning technologies used to conduct assessments is proprofs digital media. Proprof digital media equipped with HOTS questions will make students practice their thinking skills and get used to using technology. This study aims to develop an online test based on valid/feasible and practical proprofs digital media. This type of research is research and development (R&D) with the ADDIE method. The data collection technique in this study used validation sheets and response questionnaires related to the practicality of proprofs digital media. Research data analysis used ideal standard deviation for validity and readability percentage analysis for practicality. Based on the analysis results, it was concluded that the online test based on proprofs digital media is valid/feasible to use and practical in evaluating science learning.